Relevansi Pemikiran Kh. Abdurrahman Wahid Terhadap Pendidikan Islam di Era Modern - Richo Syaifullah (Nusantara: Jurnal Pendidikan Indonesia, 2021)
This study will discuss the urgency of Pancasila values in the context of life. The role of Islamic boarding schools, which has proven to be effective in educating Pancasila values. Pondok Pesantren Tremas is one of the Pesantren that is consistent in internalizing the values of Pancasila in education, both educational activities, such as those visualized in wetonan, roan and so on. This research is a Field Research, which is to get data directly from respondents by means of observation, interview, documentation and triangulation. Pondok Pesantren Tremas Arjosari, Pacitan, East Java, especially in educating Pancasila values by strengthening the basis of activities, both formally, non-formally and informally, which contain the substance of Pancasila values. Such as the activities of the santri ceremony, ngipa, roan and several other activities. As well as those that contain the values of love for the country, the value of tolerance, togetherness, divinity, mutual cooperation.